SELF ASSEMBLED CYCLODEXTRIN NANOPARTICLES AS DRUG CARRIER - PANKAJ PATIL,; SATISH ROJEKAR, (International Journal of Pharma and Bio Sciences, 2014)
Modification on cyclodextrin (CD) molecule is the basic requirement for self-aggregation. Different type of aggregates studied previously are micellar, rod shaped, hexagonal, spherical systems. Solubility of cyclodextrins can be understood by the given Highuchi-Cannor phase solubility diagram which explains the different types of CD complexes to design innovative mechanistic approaches. These self-aggregates act as effective nano-carriers in drug delivery for sustained release; targeted drug delivery; gene delivery, ophthalmic delivery, in injectable and many other systems. Different case studies in support of gene delivery, artemisinin nano-carrier system, and nanogel in ocular drug delivery have been discussed to give a better understanding of the various possibilities in CD nano carrier design. Hence this report details the different types of cyclodextrins, their chemistry, physical and chemical properties and the different modifications possible.